2013
DOI: 10.1177/0363546513493249
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Humeral Torsion and Injury in Professional Baseball Pitchers

Abstract: A strong relationship was found between lower degrees of dominant humeral torsion and more severe upper extremity injuries as well as a trend relating lower side-to-side differences in torsion with more severe dominant upper extremity injuries. In addition, there was a higher incidence of severe injuries in players with lower degrees of dominant torsion. If future studies confirm these results, humeral torsion measurements could play a role in risk assessment in pitchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
90
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 16 publications
(30 reference statements)
1
90
0
1
Order By: Relevance
“…26 Polster, et al demonstrated a 30% reduction in injury risk for every 10° of humeral retroversion of the dominant arm compared to the non-dominant arm. 25 These results suggest that GIRD due to osseous torsion may be advantageous for pitchers as humeral retroversion will allow the thrower to move through a longer throwing arc and achieve greater throwing velocity without additional physical stress to the glenohumeral joint and its supporting structures. 25 Total Rotational Motion (TRM), defined as the sum of passive glenohumeral external rotation and internal rotation at 90° of abduction in the plane of the scapula, is considered deficient if there is a side-to-side difference of more than 5°.…”
Section: Shoulder Screeningmentioning
confidence: 85%
See 4 more Smart Citations
“…26 Polster, et al demonstrated a 30% reduction in injury risk for every 10° of humeral retroversion of the dominant arm compared to the non-dominant arm. 25 These results suggest that GIRD due to osseous torsion may be advantageous for pitchers as humeral retroversion will allow the thrower to move through a longer throwing arc and achieve greater throwing velocity without additional physical stress to the glenohumeral joint and its supporting structures. 25 Total Rotational Motion (TRM), defined as the sum of passive glenohumeral external rotation and internal rotation at 90° of abduction in the plane of the scapula, is considered deficient if there is a side-to-side difference of more than 5°.…”
Section: Shoulder Screeningmentioning
confidence: 85%
“…25 These results suggest that GIRD due to osseous torsion may be advantageous for pitchers as humeral retroversion will allow the thrower to move through a longer throwing arc and achieve greater throwing velocity without additional physical stress to the glenohumeral joint and its supporting structures. 25 Total Rotational Motion (TRM), defined as the sum of passive glenohumeral external rotation and internal rotation at 90° of abduction in the plane of the scapula, is considered deficient if there is a side-to-side difference of more than 5°. 6 The odds ratio for the development of a shoulder or elbow injury in a pitcher with a TRM deficit was 2.5 and 2.6 respectively, and both were found to be statistically significant.…”
Section: Shoulder Screeningmentioning
confidence: 85%
See 3 more Smart Citations